Identification and functional characteristics of a novel splice site variant in L1CAM caused X-linked hydrocephalus - Zhou, Shijie; Zhang, Hao; Li, Xue; Chen, Quan; Xu, Zhihong (Frontiers in Genetics, 2025)
BackgroundThe L1CAM gene encodes an axonal glycoprotein belonging to the immunoglobulin supergene family that plays a crucial role in nervous system development. In this study, we reported a novel disease-causing mutation in the 3′ splice site of L1CAM and provided some insight into fetal X-linked hydrocephalus.MethodsWe obtained ultrasound images and collected samples from a couple and their fetuses. Fetal samples were acquired through amniocentesis, followed by extraction of genomic DNA. We conducted copy number variation sequencing (CNV-seq), karyotype analysis, and whole-exome sequencing The mutation site of the L1CAM gene was verified using PCR and Sanger sequencing, with splicing effects analyzed by bioinformatics analysis via BDGP, MaxEntScan and SpliceAI, as well as in vitro research via minigene assays.ResultsThe variant c.1380-1G > A in the first male fetus, located in the intron11 3′ splice site of L1CAM (chrX:153868728), led to malfunction and hydrocephalus by aberrant mRNA splicing. The ultrasound examination of the fetus revealed the presence of hydrocephalus and partial agenesis of corpus callosum. In the subsequent pregnancy, the second male fetus exhibited no mutation in L1CAM as identified by Sanger sequencing, and the ultrasound results were within normal limits. No significant findings were observed in their CNV-seq and karyotype analysis. The second fetus was delivered uneventfully and no report of hydrocephalus through the telephone follow-up for 12 months.ConclusionThis study identified the variant c.1380-1G > A in L1CAM as new pathogenic mutation for the first time according to ACMG/AMP (American College of Medical Genetics and Genomics and the Association for Molecular Pathology)-based guidelines, which caused severe fetal X-linked hydrocephalus and partial agenesis of corpus callosum. This discovery expands the mutational landscape of L1CAM-associated disorders, highlights the diagnostic utility of integrating WES into prenatal workflows for unresolved fetal anomalies, and provides actionable insights for genetic counseling in families at risk of X-linked hydrocephalus.